REVOLUTIONIZING ADMINISTRATIVE EFFICIENCY IN HIGHER EDUCATIONTHROUGH INFORMATION TECHNOLOGY IMPLEMENTATION: LITERATURE REVIEW - Nanang Zakaria; Masruri; Najamuddin Petta Solong; Alim Hardiansyah; Mohammad Ahmad Bani Amer (International Journal of Teaching and Learning, 2024)
In the dynamic landscape of higher Education, the confluence of global shifts and technological advancements propels institutions toward a critical reexamination of administrative paradigms. This literature review delves into information technology's (IT) pivotal role in orchestrating a transformative symphony, revolutionizing administrative efficiency within higher education establishments. The overarching aim is to explore the nuanced facets surrounding IT implementation, dissecting its profound impacts on administrative processes and unraveling the intricate tapestry of challenges institutions encounter in adopting these avant-garde technologies. Through an immersive traversal of existing literature, this review endeavors to distill insights into the strategic deployment and success strategies and the emergent trends shaping the landscape of IT implementation in the higher education administrative domain. The ultimate ambition is to provide a holistic understanding of information technology's implications and transformative potential for elevating administrative efficiency in the higher education echelon.